1995
DOI: 10.1128/jb.177.3.517-523.1995
|View full text |Cite
|
Sign up to set email alerts
|

The cmk gene encoding cytidine monophosphate kinase is located in the rpsA operon and is required for normal replication rate in Escherichia coli

Abstract: A gene encoding a polypeptide of 25 kDa is located immediately upstream of the gene for ribosomal protein S1, rpsA. In high gene copy number, this gene, mssA, was previously found to suppress defects in smbA, which is now known to be identical to pyrH, encoding UMP kinase. We show here that the 25-kDa polypeptide comprises CMP kinase and propose that the gene be designated cmk. In a strain deleted for cmk, the pools of CMP and dCMP were elevated approximately 30-fold. We constructed a plasmid from which synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 29 publications
1
59
0
1
Order By: Relevance
“…Sizes of protected bands were determined from standard curves of mobility plotted against the calculated sizes of the full-length probes and other RNA molecular markers (not shown) as described elsewhere (64). speB operon (17). Control hybridization reactions containing tRNA instead of mRNA showed that the apparent antisense transcription into the distal part of aroA (280-nt band in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sizes of protected bands were determined from standard curves of mobility plotted against the calculated sizes of the full-length probes and other RNA molecular markers (not shown) as described elsewhere (64). speB operon (17). Control hybridization reactions containing tRNA instead of mRNA showed that the apparent antisense transcription into the distal part of aroA (280-nt band in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CMP kinase, encoded by cmk, catalyzes the reversible interconversion of (d)CMP and (d)CDP. It is responsible for 94% of the ATPdependent CMP kinase activity in a cell extract of E. coli (9). Because the cytosine residue is synthesized in the cell from uracil at the triphosphate level, dCMP is not an intermediate in the biosynthesis of dCTP.…”
mentioning
confidence: 99%
“…The slow growth produced by a cmk mutation (Fig. 3) was previously attributed (3,9) to the kinase's role in helping to regenerate the (d)CTP that is consumed during membrane Table 1. Saturated cultures were diluted in 10 mM MgSO 4 and plated on a minimal agar containing 0.4% glucose and 1% Norit-treated Difco Casamino Acids (28), both with and without Thd at 125 g/ml.…”
mentioning
confidence: 99%
“…An amino acid sequence comparison of E. coli TMK with AMP, CMP, and GMP kinases (data not shown) has revealed significant regions of homology spanning a and c motifs as well as the invariant glycine residue (G-93 of the TMK enzyme) close to the b motif. No significant similarity of E. coli UMP kinase with E. coli TMK was found as previously described for other E. coli nucleoside monophosphate kinase (15). In fact, this enzyme appears more related to the aspartokinase family (43).…”
Section: Discussionmentioning
confidence: 53%
“…A possible involvement of this domain in protein oligomerization or allosteric regulation by nucleotides has yet to be demonstrated. The genes encoding other E. coli nucleoside monophosphate kinases specific for AMP, CMP, GMP, and UMP have been isolated and sequenced (5,15,17,43). Unlike UMP kinase which is specific for UMP, the other enzymes are active with the corresponding 2Ј deoxyribonucleotides.…”
Section: Discussionmentioning
confidence: 99%